Optimization of the surface roughness for titanium Ti6A14V in turning process using Taguchi method - Samin, R.; Azman, N; Nuawi, MZ; Haris, SM; Ghani, JA (Mattingley Publishing, 2020)
The purpose of this paper is to investigate the effect of cutting parameters on surface roughness, flank wear and chip formation using CBN tools under the conditions of turning of difficult-to-cut material, Ti6Al4V titanium alloy. Using the signal-to-noise (S / N) ratio, the Taguchi method is used to analyze the impact of cutting parameters on optimization to lower surface roughness values. The surface finish produced is very important in determining whether the quality of the machined part is within specification and permissible tolerance limits based on the flank wear and chip formation. The results shows that the cutting speed, the depth of cut and the feed rate had an impact on the surface roughness and the nose radius. It is observed that the feed rate and depth of cut values were the most significant parameters on surface roughness and cutting forces.